Democratização, comodificação e tecnologização no gênero reportagem - Oliveira, José Adriano de (2022)
The following work arose from the question about how a group of students from the 8th year of elementary school read and understand, in their textual productions, the grammatical and discursive occurrences that happen in the world, so that the corpus of this work was analyzed. from Critical Discourse Analysis. The research was based on the democratization, commodification and technologization of language, by Norman Fairclough, and its starting point is grammar and ideology in texts produced by students from reading a report. The ability to identify the intentionality of a production through vocabulary is the criterion used to analyze the essays. The choice of lexicon and the way in which such elements were used in a given circumstance were considered, taking into account the factor of origin of the motivating text and the students' reading. This way of reading and writing allowed the research to support the ACD proposal, which aims to critically analyze and form the reading and production of texts